Implementing Creative Strategies In Instagram Ads To Increase Tourezia Brand Awareness Through Social Media Platforms (Instagram) - Lintang Choiru Shifa; Murwanto Sigit (Citakonsultindo, 2024)
This research analyzes the application of creative strategies in Instagram Ads to increase Tourezia brand awareness on the Instagram social media platform. In conducting this research, the author conducted interviews and observations during his internship at Tourezia. The results show that currently Tourezia's brand awareness on Instagram is considered normal, with the company's main focus not being on the platform, but Instagram is considered as a form of existence. The problem of inorganic followers on Tourezia's Instagram is also a challenge in itself. However, Tourezia's products, especially in the Event Management and Tour Organizer categories, have succeeded in providing a clear picture of the services offered, influencing the level of awareness, and making people recognize the types of service products offered. Even though Tourezia is not focused on advertising on Instagram because its target market is B2B, not B2C, they still occasionally advertise on Instagram with the strategy of providing promotions or portfolio overviews to reach more people and increase awareness of Tourezia's existence.